2011
DOI: 10.1002/hc.20666
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of nitrilimines 1,3‐dipolar cycloaddition: Novel synthesis of spiro[4,4]nona‐2,8‐dien‐6‐one derivatives

Abstract: Regioselective 1,3-dipolar cycloaddition of nitrilimines (generated in situ from dehydrohalogenation of the corresponding hydrazonoyl halides by the action of triethylamine)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Compounds 2a-d were characterized and confirmed by comparison with literature data [18,19]. Compounds 3a, 3c, 3d, 3f, 3g, 3i, 3l, 3m, 3o, 3r, 3s and 3x [20][21][22][23][24][25][26][27][28] were prepared according to the general method and structures were confirmed via comparison with literature data. …”
Section: General Procedures For the Synthesis Of 4-arylidene-2-phenyl-mentioning
confidence: 99%
“…Compounds 2a-d were characterized and confirmed by comparison with literature data [18,19]. Compounds 3a, 3c, 3d, 3f, 3g, 3i, 3l, 3m, 3o, 3r, 3s and 3x [20][21][22][23][24][25][26][27][28] were prepared according to the general method and structures were confirmed via comparison with literature data. …”
Section: General Procedures For the Synthesis Of 4-arylidene-2-phenyl-mentioning
confidence: 99%
“…Disubstituted alkenes are typically competent substrates, with trisubstituted olefins reacting more sluggishly [ 9 ]. Nitrile imines are also effectively applied in the cycloaddition reaction with exocyclic alkenes [ 10 ] to form spirocyclic products containing 4-substituted [ 11 ] or 5-substituted pyrazole/pyrazoline cycles [ 12 ]. However, it has been shown that generally intermolecular nitrile imine cycloadditions favors the formation of a regioisomer with the most sterically encumbered substituent of the dipolarophile in the 5-position of the resulting heterocycle [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%